Coco simulator: a steady state flowsheet simulation environment / Muhammad Zimam Akid Mohd Haniffa - Zakaria, Muiz; Ismail, Nur Syazlina; Sharwazi, Nurul Balqiss Idayu; Rostam, Qasrina Syazwani (2015)
COCO simulator is an open-source chemical process simulation software which is accessible by anybody particularly students. It is claimed that this free software has similar capabilities like commercial software such as open flow sheet modelling environment incorporating unit operations, thermodynamic packages as well as reactions. In this project, the capabilities of COCO simulator are being investigated by simulating various chemical processes and then the results are compared head-to-head with those obtained by an established commercial process simulator. Several steps are used to explore this simulation, starting with the configuration and specification of the thermodynamic properties package (TEA), the reaction package (CORN), the unit operation collection (COUSCOUS) and the flow sheeting environment (COFE). The percentage error is calculated from the simulation results against those of Aspen Plus as the benchmark. The result shows the performance of COCO simulator is quite inconsistent. On one hand it gives a remarkable performance in dehydrogenation of toluene process with no errors but on the other hand it gives an erratic result in the separation of benzene and toluene process with a whopping 16.73% error. This anomaly must be investigated further in the future and it does not necessarily mean that COCO simulator is an incompetent software since this is just a preliminary study. Therefore, it is concluded that free and open-source software such as the COCO simulator is indeed able to perform similar tasks like commercial software such as Aspen Plus and thus it has some potential as alternative simulation software in chemical engineering education although its accuracy in certain task is left much to be desired.